2013
DOI: 10.3389/fnint.2013.00033
|View full text |Cite
|
Sign up to set email alerts
|

Gait analysis of teenagers and young adults diagnosed with autism and severe verbal communication disorders

Abstract: Both movement differences and disorders are common within autism spectrum disorders (ASD). These differences have wide and heterogeneous variability among different ages and sub-groups all diagnosed with ASD. Gait was studied in a more homogeneously identified group of nine teenagers and young adults who scored as “severe” in both measures of verbal communication and overall rating of Autism on the Childhood Autism Rating Scales (CARS). The ASD individuals were compared to a group of typically developing unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 34 publications
5
42
0
Order By: Relevance
“…On the basis that increased step width provides a wider base of support, and reduced velocity and step and stride lengths help a walker to keep their centre of gravity within this base of support, they argue that together these results suggest a tendency for individuals with autism to augment their stability during walking-and, therefore, that autistic children have a more unstable gait compared with typical children. Extending this research into the adolescent years, Weiss et al [38] found that 16-to 19-year olds with autism differed from typical controls with respect to various spatiotemporal aspects of gait, including step and stride length, foot positioning, cadence, velocity and step time. Hallett et al [35] report mild clumsiness of gait and reduced range of motion of the ankle in autistic adults.…”
Section: (C) Gaitmentioning
confidence: 95%
“…On the basis that increased step width provides a wider base of support, and reduced velocity and step and stride lengths help a walker to keep their centre of gravity within this base of support, they argue that together these results suggest a tendency for individuals with autism to augment their stability during walking-and, therefore, that autistic children have a more unstable gait compared with typical children. Extending this research into the adolescent years, Weiss et al [38] found that 16-to 19-year olds with autism differed from typical controls with respect to various spatiotemporal aspects of gait, including step and stride length, foot positioning, cadence, velocity and step time. Hallett et al [35] report mild clumsiness of gait and reduced range of motion of the ankle in autistic adults.…”
Section: (C) Gaitmentioning
confidence: 95%
“…The gait characteristics measured using an accelerometer attached to the body parts of a human walker are expected to describe the characteristics of individuals with ASD. The spatial and temporal characteristics measured using a walkway, such as stride length and duration variation, have been reported to differ in children with ASD compared with those in typically developing children [11]. Naruse et al [12] used an optical three-dimensional motion capture system and investigated the gait characteristics of children with attention-de cit hyperactivity disorder (ADHD), which is often a comorbid disorder linked with ASD [13].…”
Section: Introductionmentioning
confidence: 99%
“…Continuing research has only strengthened Dr. Kanner’s observations. Studies have consistently shown motor deficits across the autism spectrum (reviews\ [2-4]) including abnormalities in muscle tone, gross and fine motor skills [5-10], gait [11-15], balance [5, 14, 16], motor planning [17, 18], motor coordination and specific common tasks such as reach-to-grasp [19]. In addition, these deficits often present early in life [20-22] and may be among the most useful predictors of a future autism diagnosis [23-26].…”
Section: Introductionmentioning
confidence: 99%